2002
DOI: 10.1007/s00125-002-0840-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of integrin-matrix matching and inhibition of apoptosis on the survival of purified human beta-cells in vitro

Abstract: Aims/hypothesis. Human islet cells survive poorly in culture and are overgrown by non-endocrine cells. The aims of this study were to sort human beta cells and to develop approaches for their improved survival in culture. Methods. Human islets were infected with recombinant adenovirus expressing green fluorescent protein (GFP) under the control of the rat insulin promoter such that only beta cells expressed GFP. GFP-positive beta cells were sorted by flow cytometry, and expression of select integrins evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 50 publications
2
80
2
2
Order By: Relevance
“…We showed that two cell surface proteins (PVR and integrin αvβ3), both of which act as enterovirus receptors in established cell lines, are also expressed in primary human islets and especially in beta cells. Recently, expression of integrin subunits including αv and β3 in purified human beta cells was shown by semi-quantitative RT-PCR [61]. In contrast, no evidence was found for expression of DAF, which acts as a receptor for several of the islet cell replicating EVs in established cell lines, although different highly reactive DAF-specific monoclonal antibodies [51] were used.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that two cell surface proteins (PVR and integrin αvβ3), both of which act as enterovirus receptors in established cell lines, are also expressed in primary human islets and especially in beta cells. Recently, expression of integrin subunits including αv and β3 in purified human beta cells was shown by semi-quantitative RT-PCR [61]. In contrast, no evidence was found for expression of DAF, which acts as a receptor for several of the islet cell replicating EVs in established cell lines, although different highly reactive DAF-specific monoclonal antibodies [51] were used.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the gastrointestinal hormones gastrin, glucagon-like peptide 1 (GLP-1) and gastric inhibitory polypeptide (GIP) have been shown to induce beta cell proliferation in different in vitro models [11,[38][39][40]. However, it is difficult to directly translate these findings to the in vivo situation in adult humans, because the peptide concentrations used in those experiments were often far above the tolerable plasma concentrations in humans, and because the mitotic capacity of beta cells in culture is much higher than that of beta cells under in vivo conditions [41,42]. In the present studies, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also demonstrated high levels of cell death in dispersed islet cultures [40,44]. One explanation for the increase in cell death upon dispersion of islets into single cells is the loss of contact with the extracellular matrix (ECM), which is mediated by the integrin receptor family.…”
Section: Discussionmentioning
confidence: 99%